A system dynamics model for management of Miombo woodlands - Sumaila, U.R.; Angelsen, A.; Kowero, G.S. (Center for International Forestry Research, 2001)
The miombo woodlands of eastern, central and southern Africa are some of the most extensive dry forests in Africa. They supply a myriad of products and services for local populations, governments and the private sector, the main stakeholders. Planning the management and use of the woodlands by many and diverse stakeholders who often have conflicting interests in the woodlands continues to be a great challenge to national governments and other interested parties. This paper presents a system dynamic model, MIOMBOSIM, which has potential for facilitating planning developments in the woodlands in ways which reconcile the aspirations of the three major stakeholders. The model holds potential for analysing various policy implications on people and the woodlands, as well as the desirability of various partnership arrangements for managing and using the woodland resources.